MORFOLOGÍA VEGETAL COMO HERRAMIENTA PARA LA IDENTIFICACIÓN DE ADULTERANTES EN LOS FRUTOS COMERCIALIZADOS COMO "anís verde", Pimpinella anisum L. (Apiaceae) - Yenny GONZÁLEZ; Rosa DEGEN DE ARRUA (Federal Council of Pharmacy, 2018)
Plant morphology as a tool for the identification of adulterants in the fruit marketed as "anise", Pimpinella anisum L. (Apiaceae). Paraguay is characterized by a population that consumes largely medicinal plants for the treatment of various conditions. However, in our country there is not well-established legislation regarding the control of these products and, within this context, the question arises: the population knows what is consuming? Such situation creates a fertile ground for adulteration and substitution of all kinds. This work was developed within the framework of the project: "Identification of adulterants and foreign matter in medicinal fruits, marketed in main herbalists of Asuncion and Great Asuncion, as a contribution to the quality control of herbal drugs", funded by the Rectorado of the National University of Asuncion, and aimed to determine the presence of adulterants in the fruits marketed as "anise" Pimpinella anisum L. in main herbalists of Asuncion and Great Asuncion, using plant morphology as a tool. For this sample, the fruits of "anise" of herbalists were acquired and then analyzed in the laboratory. Two adulterants species of "anise" were identified: seeds of "sesame", Sesamum indicum and fruits of "kuratú" Coriandrum sativum; all samples showed in his one of these adulterants or even both composition, however, all sold at different prices, some even three times the value than others. Thus, morphological analysis can provide useful data when performing quality control of herbal drugs, to provide population security in what is consuming.